2015
DOI: 10.1016/j.exer.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged elevation of intraocular pressure results in retinal ganglion cell loss and abnormal retinal function in mice

Abstract: The purpose of this study was to assess the impact of prolonged intraocular pressure (IOP) elevation on retinal anatomy and function in a mouse model of experimental glaucoma. IOP was elevated by anterior chamber injection of a fixed combination of polystyrene beads and sodium hyaluronate, and maintained via re-injection after 24 weeks. IOP was measured weekly with a rebound tonometer for 48 weeks. Histology was assessed with a combination of retrograde labeling and antibody staining. Retinal physiology and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…This model mimics the pathological features of RGC damage observed in glaucoma and is a reliable model of RGC damage which can be easily assessed by measuring the nSTR response of the ERG . Following NMDA damage, we observed a reduction in the nSTR and a slight elevation in the b‐wave of the ERG, which is characteristic of similar glaucoma models . We observed a partial but significant restoration of the nSTR after transplantation of the highest dose of cells used (1 × 10 5 ).…”
Section: Discussionsupporting
confidence: 61%
“…This model mimics the pathological features of RGC damage observed in glaucoma and is a reliable model of RGC damage which can be easily assessed by measuring the nSTR response of the ERG . Following NMDA damage, we observed a reduction in the nSTR and a slight elevation in the b‐wave of the ERG, which is characteristic of similar glaucoma models . We observed a partial but significant restoration of the nSTR after transplantation of the highest dose of cells used (1 × 10 5 ).…”
Section: Discussionsupporting
confidence: 61%
“…IOP was recorded using a rebound tonometer optimized for mouse use (Tonolab) under isoflurane anesthesia as previously described (Frankfort et al, 2013; Khan et al, 2015; Pease et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…The hallmark of glaucoma is the apoptosis of retinal ganglion cells (RGCs), which are the only efferent neurons that convey visual signals from the retina to the brain. Several risk factors, including elevated intraocular pressure (2), oxidative stress (3), elevated glutamate (4) and aging (5), have been considered to accelerate RGC apoptosis in glaucoma, among which, oxidative stress is considered as the final common pathway in glaucoma (6). Several studies have reported that oxidative stress can lead to apoptosis of RGCs through activation of the mitochondrial pathway (7), and that apoptosis is the main cause of RGC loss (8).…”
Section: Introductionmentioning
confidence: 99%